A nationwide skin protection program introduced in hairdressing vocational schools was followed by a decreased risk of occupational hand eczema - Havmose, Martin; Uter, Wolfgang; Gefeller, Olaf; Friis, Ulrik F.; Thyssen, Jacob P.; Zachariae, Claus; Johansen, Jeanne D. (Contact Dermatitis, 2022)
Background: Compliance with glove use and safe work practices are important factors in primary prevention of occupational hand eczema (OHE) in hairdressers. Objective: To assess the risk OHE and compliance with skin protective measures in hairdressers trained before and after implementation of a nationwide skin protection program in Danish hairdressing vocational schools in 2011. Methods: A repeated cross-sectional study was performed. A questionnaire was sent in 2009 and 2020. The Danish Labour Market Supplementary Pension Scheme provided information on yearly payments from the hairdressing profession. Results: A response rate of 66.6% (305/460) was obtained in the 2009 survey and of 29.9% (363/1215) in the 2020 survey. The career time prevalence of OHE decreased from 42.8% to 29.0% (adjusted odds ratio 0.55 95% confidence interval [CI] 0.40-0.77) and the incidence rate of OHE decreased from 57.5 (95%CI 48.4-68.4) to 42.0 (95%CI 34.6-50.9) per 1000 person years (incidence rate ratio 0.73 [95%CI 0.56-0.95] between the two surveys). A statistically significant (P <.05) increase in glove use when doing wet-work and when handling hair dyes, permanent wave solutions and bleaching products was observed in the 2020 compared to the 2009 survey. Conclusion: Our data suggest that skin protection training during apprenticeship reduces the risk of OHE in hairdressers. The lack of primary prevention of OHE in hairdressing vocational schools may be a missed opportunity in the prevention of the disease.
CRIS-Team Scopus Importer:2022-10-14
Keywords: contact dermatitis; disposable gloves; hairdressers; occupational; primary prevention